Komparasi Motivasi Belajar Siswa Mi Al-Huda II Kedamean Pada Pembelajaran Luring Dan Daring Masa Pandemi - Abdur Rahman; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
Learning motivation is a form of driving force that converts energy, both from outside and from within a person that is useful for generating learning activities, and giving direction to these learning activities into real activities to achieve a goal. The aims of this study were to: 1) determine the learning motivation level of MI Al-Huda II students when offline learning took place, 2) determine the learning motivation level of MI Al-Huda II students when online learning took place, 3) and find out the comparison of MI students' learning motivation Al-Huda II when offline learning and online learning took place. The method used in this study is a quantitative method, the type of research is comparative. The data collection technique uses a questionnaire. The data analysis technique is by instrument testing, prerequisite testing, and statistical descriptive percentage testing using the T-Paired Test formula. The results of the study showed that: 1) the level of student motivation when offline learning was in the low category with 5 children (16%), in the medium category there were 21 children (68%), and in the high category there were 5 children (16%). 2) the level of student motivation when learning online is in the low category with a total of 6 children (19%), in the medium category there are 19 children (61%), and in the high category there are 6 children (20%). 3) there is a significant difference in the learning motivation of MI Al-Huda II Kedamean Gresik 2020-2021 students when learning offline and when learning online. This is evidenced by the results of the T-Test test obtained tcount > ttable, tcount = 2.097 > ttable 2.0423, then Ho is rejected and Ha is accepted.